The general election of 2022: the return of bipolarity?. Issue 2 (3rd April 2023) - Russo, Luana; Vegetti, Federico
ABSTRACT: The 2022 Italian parliamentary elections were largely pictured, especially by the foreign press, as an alarming victory for the extreme right. In this article, we argue that though the 26% obtained by Brothers of Italy was surely an outstanding result, it does not automatically imply that the Italian electorate shifted further to the right in terms of its preferences and ideology. The evidence we present seems rather to suggest that this result is the consequence of Brothers of Italy's electoral partners, the Lega and Forza Italia, losing their appeal among the centre right's voters. This, along with an electoral law that favours bipolarity, and division among the remaining coalitions, led to an outstanding victory for the centre right (right-centre?).